THE EFFECT OF TEACHER ORGANIZATIONAL ACTIVITY OF ADOLESCENT RED (PMR) ON EFFECTIVE TALKING ABILITY STUDENT CLASS XI SMA NEGERI 2 PANCA RIJANG DISTRICT SIDENRENG RAPPANG - Musyawir Musyawir; Saiful Malul (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2018)
AbstractThis study aims to determine whether or not there is any impact of the activity of red cross youth organization to the effective speaking ability of the students of class XI SMA Negeri 2 Panca Rijang Sidenreng Rappang Regency. This research uses two variables, namely the activity of the red cross youth organization as independent variabel (experimental group) and the ability to speak effective as a dependent variabel (control group). The population in this study is all students of class XI SMA Negeri 2 Panca Rijang Sidenreng Rappang Regency as many as 193 students, while the sample is 15% of the total population, which is 30 students. Data collection technique in this studi, ie documentation techniques then the results obtained from these techniques are further analyzed and processed through descriptive statistical techniques in the form of mean.The results showed that the value Mx = 68,3 and My = 63 so it can be seen that the value of Mx greater than My, ie 68,3 >63. Based on the result of data analysis, it can be concluded that there is impact of activity of organization of red cross yout organization to ability of effective speaking of student of class XI Negeri 2 Panca Rijang Sidenreng Rappang Regency.Keywords: Activity, Youth Red Cross organization, Speak effectively